2015
DOI: 10.1056/nejmra1502824
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Complications in Patients Undergoing Major Noncardiac Surgery

Abstract: lthough major noncardiac surgery has the potential to improve the quality and prolong the duration of a patient's life, surgery may also precipitate complications such as death from cardiac causes, myocardial infarction or injury, cardiac arrest, or congestive heart failure. 1 In this article, we review what is known about the epidemiology and mechanisms of perioperative cardiac complications (i.e., from induction of anesthesia to within 30 days after surgery), preoperative methods of predicting these complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
279
1
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(330 citation statements)
references
References 94 publications
4
279
1
22
Order By: Relevance
“…Prior coronary stenting is a well-established risk factor associated with major adverse cardiac events. 1,[16][17][18][19] More recently, however, Holcomb and colleagues demonstrated that the incremental risk of cardiac complications significantly decreases when surgery is performed more than 6 months following coronary stenting: the incremental risk of cardiac complications stabilizes at 1% beyond 6 months following coronary stenting. 20 Although NSQIP excludes those with prior percutaneous coronary intervention within 6 months of hepatectomy, we still found that those with history prior PCI (>6 months before the liver resection) had a cardiac complication rate of 6.4% as well as a three-fold increase risk of cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior coronary stenting is a well-established risk factor associated with major adverse cardiac events. 1,[16][17][18][19] More recently, however, Holcomb and colleagues demonstrated that the incremental risk of cardiac complications significantly decreases when surgery is performed more than 6 months following coronary stenting: the incremental risk of cardiac complications stabilizes at 1% beyond 6 months following coronary stenting. 20 Although NSQIP excludes those with prior percutaneous coronary intervention within 6 months of hepatectomy, we still found that those with history prior PCI (>6 months before the liver resection) had a cardiac complication rate of 6.4% as well as a three-fold increase risk of cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…1 Preoperative cardiac disease is a well-known risk factor associated with poor surgical outcomes following vascular 2,3 and colorectal surgery. [4][5][6] The risk of mortality increases 5-fold in patients with prior ischemic heart disease undergoing non-cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the clinical characteristics of patients who undergo non cardiac surgery are available in the international literature. Guidelines recommend standardized management protocols for elderly surgery patients and diverse strategies have been proposed for assessing the preoperative risk in the more advanced ages [5][6][7][8]. Also in Italy, several studies have documented the impact of elderly age in non cardiac surgery and, in particular, the problem of comorbidity [2,9].…”
Section: Importance Of the Issue And Epidemiological Datamentioning
confidence: 99%
“…Unstable atherosclerotic plaque rupture leading to thrombus formation and stress induced ischemia due to mismatch between the myocardial oxygen supply and demand during intubation or intraoperative tachycardia (due to hypotension or bleeding) are the main mechanisms of perioperative cardiac complications (1,3).…”
Section: Introductionmentioning
confidence: 99%